VLSI design and test : 21st International Symposium, VDAT 2017, Roorkee, India, June 29-July 2, 2017, Revised selected papers /: 21st International Symposium, VDAT 2017, Roorkee, India, June 29-July 2, 2017, Revised selected papers. (2017) - Unknown
No abstract available